Effect of temperature on stamen culture and somatic plant regeneration in rubber - Yun W Z; Ting C X (Acta Agronomica Sinica, 1995)
In stamen culture experiments, a temperature difference of only 2 degree C could cause marked differences in efficiency. High temperatures could enhance callus formation rate but reduce callus differentiation ability, resulting in a lower plantlet induction rate owing to reduced embryoid quantity and quality. They could also accelerate root development, causing the root to appear before the shoot in some cases and thus impairing further embryoid development. Optimum temperatures were 24 to 27 degree C depending on the stage of culture. The temperatures most suitable for callus induction, somatic embryogenesis and plant regeneration were (respectively) 26, 24-25 and 26-27 degree C. Regeneration frequencies as high as 40.5;were obtained by using these optimum temperatures.
Source Year: 1996
Keywords: Rubber; Somatic plant regeneration; Stamen culture